Annual World Bank Conference on Development Economics 2001/2002 (Annual World Bank Conference on Development Economics, 2002)
The Annual World Bank Conference on Development Economics (ABCDE) is a global gathering of the world's leading scholars and development practitioners. Among the attendees were participants from developing countries, universities, think tanks, nongovernmental organizations, and international financial institutions. The 13th annual conference, held in May 2001, concentrated on the current thinking in development policy and the implications for the global economy with a particular focus on the two important and controversial themes of globalization and health. This book is a collection of conference papers from this forum